Bank specific factors and non-performing loans Evidence from licensed commercial banks in Sri Lanka. - Subramaniam, V.A.; Anandasayanan, S.; Kasthuri, S. (University of Jaffna, 2022)
Lending is one of the prominent functions of banks as loans make up the bulk of their assets. Still, lending is not the easy process which may lead to credit risk and create the issue of non-performing loan (Ismail and Rahman, 2021). When the banks release the loans to customers, due and prompt care should be taken on by considering the credibility of the customers in order to prevent the default cases in advance (Jie et.al 2016). Non-performing loans are the financial assets which do not produce any interest or principal repayment for the banks. The non-performing loans are the loans which are not paid to the bank after 90 days (Eletter and Yaseen, 2017). For the purpose of ensuring financial stability, financial intermediaries should minimize their non-performing loans. The objective of this study is to identify the impact of bank specific factors on the non-performing loans of licensed commercial banks in Sri Lanka. 11 Licensed commercial banks in Sri Lanka were considered as sample for the study. In this study liquidity, profitability, board size, capital adequacy and loan growth are considered as independent variables and non-performing loan is considered as dependent variable. Sri Lanka’s non-performing loans ratio was 4.7 % in December 2019, compared with the ratio of 3.4 % in the preceding year. The analysis of Sri Lanka’s non performing loans ratio data for the period from 1998 to 2019 reveals that the ratio reached an all time high of 15.8 % in 1999 and a record low of 2.5 % in 2017. Thus, there is a need to identify the determinants of the non- performing loans and take necessary actions to avoid non- performing loan issues in future. As worldwide, banks have been facing the challenges of managing credit risk resulting in greater amount of default rate due to the COVID 19 pandemic arose in December 2019. In the context of Sri Lanka, as per the Central Bank report it can be noticed there has been continuous increase in the non-performing loans of commercial banks in Sri Lanka. Therefore, it is utter most important to identify the factors influencing on non-performing loans of licensed commercial banks in Sri Lanka.